The Effect of Promotion, Discount, Service Quality on Consumer Satisfaction through Purchase Decisions on E-commerce as Intervening Variables on Students of the Faculty of Economics, UNM - Rijal, Syamsu; Hidayah, Resky Wira; Mustari; Tadampali, Andi Caezar To; Purnamasari, Wulan (PT. LITERASI SAINS NUSANTARA, 2024)
E-commerce has become an inseparable part of people's daily lives. Nowadays, more and more consumers choose to shop online, which provides more business opportunities for e-commerce companies and also gives consumers more choices. The purpose of this study is to gain broader knowledge and understanding of the influence of promotions, discounts, service quality on consumer satisfaction through purchasing decisions on e-commerce as intervening variables in students of the Faculty of Economics and Business, State University of Makassar. The method used in this study is a quantitative research technique with a descriptive research type. The sample used in this study was 100 respondents. The data analysis technique used is the Partial Least Square Structural Equation Model (PLS-SEM). The results of this study show that promotion, discount, service quality have a positive and significant influence on consumer satisfaction. Likewise, purchasing decisions have a positive impact on consumer satisfaction. Purchasing decisions are able to mediate the relationship between promotion, discount, service quality on consumer satisfaction.